PENGARUH MEDIA POWERPOINT TERHADAP PEMAHAMAN MATERI AKIDAH AKHLAK SISWA KELAS V DI MIS AL- HIKAMUSSALAFIYAH KARAWANG - Rara Magfirotun Nisa; Astuti Darmiyanti; Abdul Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of computer-based learning media using PowerPoint on students’ understanding of Aqidah Akhlak material at MIS Al-Hikamussalafiyah Karawang. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of 46 fifth-grade students divided into an experimental class and a control class. Data were collected through pretests, posttests, observations, and documentation. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, Mann–Whitney U tests, and N-Gain analysis. The results showed that the average pretest score of the experimental class was 12.09 and increased to 16.87 in the posttest, while the control class increased from 11.00 to 14.73. The N-Gain score of the experimental class was 0.6791, which was higher than the control class score of 0.4932. The Mann–Whitney U test produced an Asymp. Sig. (2-tailed) value of 0.041 < 0.05, indicating a significant effect of PowerPoint-based learning media on students’ understanding of Aqidah Akhlak material. Therefore, PowerPoint can be used as an effective learning medium to improve students’ understanding in Islamic Religious Education learning.